Myocardial gallium-67 citrate scintigraphy in patients with systemic sclerosis. - Gaál, J (1995)
OBJECTIVE--To detect myocardial involvement in 16 patients with systemic sclerosis using radiogallium scintigraphy METHODS--Sixteen patients with systemic sclerosis were investigated by myocardial gallium-67 citrate scintigraphy. Echocardiographic studies and (in the positive cases) magnetic resonance imaging were also performed. RESULTS--Increased myocardial gallium uptake was found in five of the 16 patients. None of these positive cases exhibited any 'classical' clinical, electrocardiographic or laboratory signs characteristic of myocarditis. The mean age of the positive cases was 60.8 (SD 5.0) years compared with 44.6 (10.7) years for the negative cases; no difference was detected in the mean disease duration between these two groups. Two of the affected cases belonged to the limited scleroderma subgroup. CONCLUSIONS--In spite of the low number of patients investigated, it is tempting to speculate that elderly patients with a disease onset around 60 years tend to be the candidates in whom a positive gallium-67 scintigraphy test may best indicate a silent myocardial interstitial inflammation.